2019
DOI: 10.1080/14756366.2019.1615485
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity and p53 upregulation effects of chalcones on human breast cancer cells

Abstract: Chalcones are valuable structures for drug discovery due to their broad bioactivity spectrum. In this study, we evaluated 20 synthetic chalcones against estrogen-receptor-positive breast cancer cells (MCF-7 line) and triple-negative breast cancer (TNBC) cells (MDA-MB-231 line). Antiproliferative screening by MTT assay resulted in two most active compounds: 2-fluoro-4'-aminochalcone (11) and 3-pyridyl-4'-aminochalcone (17). Their IC 50 values ranged from 13.2 to 34.7 mM against both cell lines. Selected chalcon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 47 publications
2
35
0
1
Order By: Relevance
“…The anticancer activity of 4′-amino-1-naphthyl- chalcone and 4′-amino-4-methyl-1-naphthylchalcone described by Seba et al proved the ability of these derivatives to inhibit the migration and invasion of osteosarcoma cells, especially in p53-expressing cells (U2OS) [22]. Moreover, Santos et al showed that aminochalcones containing a fluorine atom at the C-2 position and a pyridyl group at the C-3 position induced apoptosis due to upregulated p53 protein expression in the breast cancer cell lines MCF-7 (ER) and MDA-MB-231 (TNBC) [23]. The studies of Pati et al proved that incorporation of an amino moiety into the ring B of the methoxychalcones may increase their cytotoxicity against a murine melanoma cell line (B16) with the effect depending on the location of the substituent [10].…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer activity of 4′-amino-1-naphthyl- chalcone and 4′-amino-4-methyl-1-naphthylchalcone described by Seba et al proved the ability of these derivatives to inhibit the migration and invasion of osteosarcoma cells, especially in p53-expressing cells (U2OS) [22]. Moreover, Santos et al showed that aminochalcones containing a fluorine atom at the C-2 position and a pyridyl group at the C-3 position induced apoptosis due to upregulated p53 protein expression in the breast cancer cell lines MCF-7 (ER) and MDA-MB-231 (TNBC) [23]. The studies of Pati et al proved that incorporation of an amino moiety into the ring B of the methoxychalcones may increase their cytotoxicity against a murine melanoma cell line (B16) with the effect depending on the location of the substituent [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their various biological and pharmacological properties, chalcones and its derivatives are intensely involved in the medicinal and industrial aspects [ 81 ]. Natural and synthetic chalcones exhibit a wide variety of biological properties including anti-proliferative [ 82 ], anti-inflammatory [ 83 ], anti-cancer [ 84 ], anti-tubercular and anti-bacterial [ 85 ], anti-fungal [ 86 ], anti-oxidant [ 87 ] and anti-leishmanial activities [ 88 ]. In addition, naturally occurring chalcones are precursors in the biosynthesis of chromanones and flavanones and play a significant role in the plant protection against ultraviolet radiation, diseases and insects [ 89 ].…”
Section: An Overview Of Chalcones Derivatives As Possible Therapeuticmentioning
confidence: 99%
“…Moreover mechanisms of action of bioactive compounds isolated from A. pindrow also needs to be further explored for clarity of pharmacological actions. There has been reports from various studies that chalcones behave as strong antioxidants [69,70] and antiproliferative activities [71,72]. Since chalcones have been isolated from the barks of A. pindrow, investigations on anticancer and antiproliferative activity also needs to be undertaken for development of anticancer drug.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%